2014
DOI: 10.1177/003335491412900210
|View full text |Cite
|
Sign up to set email alerts
|

High Risk for HIV following Syphilis Diagnosis among Men in Florida, 2000–2011

Abstract: Men who acquire syphilis are at very high risk of HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 18 publications
0
38
1
3
Order By: Relevance
“…Among men with syphilis, studies in New York City and Florida have found high rates of subsequent HIV infection after the syphilis diagnosis (annual incidence of 3.6% and 2.3%, respectively). 22,23 Annual incidence was even higher (5.6%) among MSM after a diagnosis of syphilis. 22 Taken together, these data indicate that persons diagnosed as having syphilis should be evaluated for ongoing risk of HIV infection and, if appropriate, targeted for HIV prevention services and considered possible candidates for preexposure prophylaxis (PrEP).…”
Section: Discussionmentioning
confidence: 94%
“…Among men with syphilis, studies in New York City and Florida have found high rates of subsequent HIV infection after the syphilis diagnosis (annual incidence of 3.6% and 2.3%, respectively). 22,23 Annual incidence was even higher (5.6%) among MSM after a diagnosis of syphilis. 22 Taken together, these data indicate that persons diagnosed as having syphilis should be evaluated for ongoing risk of HIV infection and, if appropriate, targeted for HIV prevention services and considered possible candidates for preexposure prophylaxis (PrEP).…”
Section: Discussionmentioning
confidence: 94%
“…The high rate of incident syphilis and prior syphilis infection among MSM in our population is relevant since uninfected male partners who acquire syphilis have a significant short-term risk of HIV acquisition (3.6% within first year). [36,37] This study does not confirm findings from 2005 and 2016 showing that HIV-infected MSM are more likely to engage in unprotected sex after EDM prescription. [11,13] This deviation from the literature may be due to a benefit of EDM prescription within a community care clinic that focuses on HIV treatment and prevention.…”
Section: Discussionmentioning
confidence: 59%
“…A study of men diagnosed with early syphilis in Florida in 2003 found 21.5% were reported with new HIV infection by the end of 2011. 16…”
Section: Discussionmentioning
confidence: 99%